Supply Chain Management (SCM): Disintegration Team Factors in Malaysian Industrialised Building System (IBS) Construction Projects - Mohd Nawi, Mohd Nasrun; Lee, Angela; Mydin, Md Azree Othman; Osman, Wan Nadzri; Rofie, Mohamad Khadafi (ExcelingTech Publishers, 2018)
Malaysia as a developing country, is driving for implementing a new or modern construction method called Industrialised Building System (IBS), as an alternative towards enhancing construction productivity.The level of implementation of IBS however is still below the Government target.One of the key barriers of its implementation is related to project delivery and supply chain issues.The majority of IBS project developments in Malaysia are still conducted using the traditional construction process approach, which has resulted in a failure to form effective teams and thus impacted on a number of issues such as delay, wastages, and lack of communication and coordination.This paper, through the use of industry workshops, aims to validate this issue and investigate how far it affects the process of IBS implementation.Suggestions on how an integrated approach in design and construction in order to minimise the fragmentation gaps will be concluded.